2008
DOI: 10.1093/eurheartj/ehn099
|View full text |Cite
|
Sign up to set email alerts
|

Safety of percutaneous coronary intervention during uninterrupted oral anticoagulant treatment

Abstract: Our study shows that PCI is a safe procedure during UAC with no excess bleeding complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
47
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 27 publications
6
47
0
5
Order By: Relevance
“…This is particularly important as the scheme of DAPT was proposed as a standard of treatment before conducion of studies on this population of patients [2]. Most of the reports regarding the risk of combined therapy with DAPT comes from the studies on patients with acute coronary syndrome [3,[19][20][21][22]. It is known that bleeding complications are observed in 2-8% of patients with coronary artery disease and are more frequent in women, in elderly, in patients with renal dysfunction and those with a history of bleeding [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is particularly important as the scheme of DAPT was proposed as a standard of treatment before conducion of studies on this population of patients [2]. Most of the reports regarding the risk of combined therapy with DAPT comes from the studies on patients with acute coronary syndrome [3,[19][20][21][22]. It is known that bleeding complications are observed in 2-8% of patients with coronary artery disease and are more frequent in women, in elderly, in patients with renal dysfunction and those with a history of bleeding [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that bleeding complications are observed in 2-8% of patients with coronary artery disease and are more frequent in women, in elderly, in patients with renal dysfunction and those with a history of bleeding [3][4][5]. Many studies confirmed that the use of DAPT with oral anticoagulants efficiently reduces the risk of recurrent coronary incidents, but is related to worse prognosis due to increased risk of bleeding [19][20][21][22]. Chronic use of triple anticoagulant therapy (TAT) in population of patients > 75 years of age is related to 15% risk of bleeding complications per each year of treatment [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…67 Continuation of VKA (with the INR within the therapeutic range) is also recommended for PCI in the setting of an acute coronary syndrome (ACS). [64][65][66]68 However, NOACs should be temporarily discontinued in all patients presenting with an ACS.…”
mentioning
confidence: 99%